Optimization of car crankshaft strength with ductile iron material through Solidworks simulation - Kimal Al Ghifari (Researcher and Lecturer Society, 2024)
This study aims to provide crucial insights into the performance of crankshaft designs under various loads and operational conditions. The method employed in this research is finite element analysis, facilitated by SolidWorks software, utilizing Ductile Iron material. Crankshafts crafted from ductile Iron are typically employed in vehicle engines due to their commendable mechanical properties and cost efficiency. The force exerted by the piston on the crankshaft generally ranges from 4500 N to 7500 N. The Factor of Safety within the crankshaft denotes the ratio between its material strength and the maximum stress it experiences during operation. The findings of this research indicate that the highest recorded maximum von Mises stress utilizing ductile iron material is 4.658 MPa, with a corresponding Factor of Safety in the crankshaft of 118.4. Consequently, the resilience of ductile iron crankshafts under varying loads and operational conditions can be ensured through meticulous analysis of crankshaft geometry.